Chronic Epstein Barr virus infection leading to classical Hodgkin lymphoma. Issue 1 (December 2016) - Sarwari, Nawid; Khoury, Joseph; Hernandez, Cristhiam
Abstract Background Chronic Epstein Barr virus (EBV) infection in an immunocompetent host has been described however it is not a common entity. It has been linked to many lymphoproliferative disorders and achieves such via many molecular mechanisms, some of which are poorly understood. In addition to infectious mononucleosis, the EBV is linked to various other hematological pathologies and autoimmune disorders. Case presentation We describe the case of an elderly immunocompetent female who presented with non-specific symptomatology, lymphadenopathy, cytopenias, elevated autoantibody titers and a crescent EBV viral load that were suggestive of a multisystemic inflammatory disease related to EBV. Extensive work up including multiple bone marrow biopsy and lymphoid tissue procedures ultimately led to the diagnosis of Hodgkin lymphoma. Conclusion EBV-related lymphomagenesis is complex and through the utilization of its nuclear antigens and latent membrane proteins the virus is able to shape the microenvironment to promote the various pathologies seen. Moreover, the diagnosis of EBV-associated lymphoproliferative disorders might be challenging when they present in immunocompetent individuals. Our case also represents an emphatic reminder for clinicians that spontaneous regression of lymphadenopathy is not exclusive of low-grade lymphoid malignancies.